STRATEGI PENGEMBANGAN KOMODITAS PERTANIAN UNGGULAN DI KECAMATAN KALITIDU KABUPATEN BOJONEGORO - RAHAYU, WIWIT (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2011)
This study aims to identify the classification of agricultural commodities in Kalitidu Subdistrict, Bojonegoro Regency and formulate alternative development strategy of pre-eminent agricultural commodities in Kalitidu Subdistrict Bojonegoro Regency. The basic method used in this research is analytical descriptive method. Data used in this study are primary and secondary data. Data analysis methods used are (1) Klassen Typology analysis to determine the classification of agricultural commodities and (2) SWOT analysis to identify internal and external factors and alternative strategies in the development of pre eminent agricultural commodities.